Membaca Ulang Ayat Poligami: Sebuah Pembacaan Sinkronik-Diakronik - Fuady; Umami, Khoirul (Program Studi Ilmu Al-Quran dan Tafsir STIU Darul Quran, 2024)
The discourse of polygamy is a discourse that is always hotly discussed. This is because this is a very sensitive issue and is in direct contact with people from various circles, both academics and grassroots communities. The debate surrounding the legality of the practice of polygamy has never found agreement. Various methods and approaches are proposed to look at the actual law of polygamy, ranging from hermeneutics, maqasid al-shariah, to contextual approaches.. However, there are still no academics who try to capture the chronological series of polygamy practices from pre-Islamic times to the presence of Islam and dialogue polygamy verses with jahiliah traditions. Departing from this, this research seeks to reorganize QS. An-Nisa' [4]: 3 by using a synchronic-diachronic approach. This research uses a qualitative method and produces two points of conclusion, 1). The chronology of the polygamy verse begins when Islam dialogues with issues of gender equality in the climate of ignorance, and polygamy is one of the ignorant traditions that is not abrogated and only given regulation, 2). Synchronically, the background of polygamy restrictions is caused by the economic insecurity of men who cause new problems for others. (taking the property of orphans who are cared for to be given to their wives as maintenance). In addition, in the records of the books of hadith, psychologically, the Prophet really hoped to have a people of his own. Forbidding polygamy is like closing the door on the Prophet's hopes.